The Differences in the Performance Profiles Between Native and Foreign Players in the Chinese Basketball Association - Wang, Xing; Han, Bin; Zhang, Shaoliang; Zhang, Liqing; Lorenzo Calvo, Alberto; Gomez, Miguel-Ángel (Frontiers in Psychology, 2022)
The aim of the study was to (i) use the clustering analysis method to classify and identify the native and foreign basketball players into similar groups based on game-related statistics; (ii) use the Pearson's Chi-square test to identify the key clusters that affect whether a team enters the playoffs; and (iii) use the classification tree analysis to stimulate the prediction of team ability and the construction of the team roster. The sample consisted of 422 foreign players and 1,775 native players across 9 seasons from 2011 to 2019. The clustering process allowed identifying nine native and six foreign player performance profiles. In addition, two clusters (p < 0.001, ES = 0.33; p < 0.001, ES = 0.28) of native players and one cluster (p <0.05, ES = 0.16) of foreign players were identified that had a significant impact on the team ability. These results provide alternative references for basketball staff concerning the process of evaluating native and foreign players performance in Chinese Basketball Association.